THE ROLE OF ACCOUNTING CONSERVATISM AS A MODERATE OF DEBT RATIO EFFECT ON FINANCIAL DISTRESS - Yuni Sukandani; Siti Istikhoroh; Ulfa Puspa Wanti Widodo; Nurba'itty Ning Syahdu (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2021)
The purpose of this study is to determine the role of accounting conservatism as a moderating between debt ratio and financial distress. Measurement of debt ratio variables using the debt to asset ratio, financial distress using Z-Score analysis, and accounting conservatism using the accrual model. Financial statements of 8 plastic and packaging companies listed on the Stock Exchange are used as population and samples with a purposive sampling technique. Data analysis using Moderated Regression Analysis (MRA) with hypothesis testing t test. The first test results obtained a significant level of 0,000 is smaller than 0,05 (0,000 < 0,05) meaning that the debt ratio affects financial distress. While the second test obtained a significant level of 0,108 is greater than 0,05 (0,108 > 0,05) which means that accounting conservatism is not able to moderate the ratio of debt and financial distress. Iis expected to be useful as a reference source, especially related to the application of accounting conservatism, so that it can be used as a material consideration for companies in applying for loans and anticipating financial distress.